A comprehensive assessment of the musculoskeletal system: The CAMS-Knee data set - Taylor, R.; Schütz, P.; Bergmann, G.; List, R.; Postolka, B.; Hitz, M.; Dymke, J.; Damm, P.; Duda, G.; Gerber, H.; Schwachmeyer, V.; Hosseini Nasab, S. H.; et al. (Journal of Biomechanics, 2017)
Combined knowledge of the functional kinematics and kinetics of the human body is critical for understanding a wide range of biomechanical processes including musculoskeletal adaptation, injury mechanics, and orthopaedic treatment outcome, but also for validation of musculoskeletal models. Until now, however, no datasets that include internal loading conditions (kinetics), synchronized with advanced kinematic analyses in multiple subjects have been available. Our goal was to provide such datasets and thereby foster a new understanding of how in vivo knee joint movement and contact forces are interlinked - and thereby impact biomechanical interpretation of any new knee replacement design. In this collaborative study, we have created unique kinematic and kinetic datasets of the lower limb musculoskeletal system for worldwide dissemination by assessing a unique cohort of 6 subjects with instrumented knee implants (Charité - Universitätsmedizin Berlin) synchronized with a moving fluoroscope (ETH Zürich) and other measurement techniques (including whole body kinematics, ground reaction forces, video data, and electromyography data) for multiple complete cycles of 5 activities of daily living. Maximal tibio-femoral joint contact forces during walking (mean peak 2.74 BW), sit-to-stand (2.73 BW), stand-to-sit (2.57 BW), squats (2.64 BW), stair descent (3.38 BW), and ramp descent (3.39 BW) were observed. Internal rotation of the tibia ranged from 3° external to 9.3° internal. The greatest range of anterio-posterior translation was measured during stair descent (medial 9.3 ± 1.0 mm, lateral 7.5 ± 1.6 mm), and the lowest during stand-to-sit (medial 4.5 ± 1.1 mm, lateral 3.7 ± 1.4 mm). The complete and comprehensive datasets will soon be made available online for public use in biomechanical and orthopaedic research and development.